Important Psychological Factor of Sports Player: The Importance of Sports Psychology in Enhancing Performance (Journal of Advances and Scholarly Researches in Allied Education, 2019)
For reaching high levels of sports, the psychology of the sports participant is quite critical. It requires many physical, behavioral, moral and emotional elements of the athlete. The different facets of psychology require personality sport often entails behavior, fear, violence and tension. In this study we have discussed about the role of sports psychology, development trend of competitive sports psychology, benefits of sports psychology and important psychological factors which effect the physical performance which is concluded that sports psychology is necessary and should be employed in the scientific training of athletes for performance enhancement.